Proposição de observatório científico para popularização da Ciência - Farias, Maria Giovanna Guedes (2020)
It aims to discuss the aspects and concepts related to scientific popularization, in order to propose the creation of a scientific observatory for the Federal University of Ceará, which could serve as a model for other teaching and research institutions. This objective was built with the following concerns: society’s ignorance of the relevance of science in development and social progress, as well as the increase in the lack of confidence and mistrust in the results of research undertaken by universities, institutes and research centers. Regarding the methodological path, a literature review was carried out focusing on the concepts: scientific observatory, dissemination, diffusion, dissemination and popularization of science, in order to outline a proposal for the construction of the observatory, with the establishment of a composition basic formed by the items: planning, structure, institutional aspects, popularization and approximation actions. Thus, it is expected that scientific knowledge can be disseminated, understood and used, constituting itself as a producer of meaning for society. It is concluded that an observatory for the popularization of science contributes, greatly, to create and increase the public perception of Brazilians about science, collaborating so that the population feels more interested, integrated and co-participates in the scientific knowledge production process.